Electrical circuit modeling for the relaxor response of bismuth magnesium tantalate pyrochlore - Tan, P.Y.; Tan, K.B.; Khaw, C.C.; Murthy, H.C. Ananda; Balachandran, R.; Chen, S.K.; Lee, O.J.; Chan, K.Y.; Lu, M. (Elsevier, 2024)
The electrical properties of bismuth magnesium tantalate pyrochlore, Bi3.30Mg1.88Ta2.82O13.88 (BMT) were investigated by both inductor-capacitor-resistor (LCR) and impedance spectroscopy techniques covering a broad temperature range of 10–1073 K and a frequency range of 5 Hz - 1 MHz. At below ∼180 K, BMT pyrochlore exhibited interesting relaxor behaviour that showed high dispersion characteristics in its frequency-temperature dependent dielectric constants, ε′ and dielectric losses, tan δ, respectively. The maximum ε′max of ∼77 was obtained at the temperature maximum, Tm of 154 K. The frequency-independent ε′ data above 154 K at a fixed frequency of 1 MHz can be well fitted with the Curie-Weiss law and the relaxation features of Bi3.30Mg1.88Ta2.82O13.88 obeyed the Vogel-Fulcher equation. The dielectric properties of Bi3.30Mg1.88Ta2.82O13.88 relaxor in the low temperature range of 20–320 K could be satisfactorily modeled with different equivalent circuits. In this perspective, a master circuit consisting of a parallel R-C-CPE element in series with a capacitor was required to accurately fit the low temperature data.